Promotion and quality of service regarding employment social security program decisions through agency image - Taufiq Nurrahman; Rr. Ratna Roostika (Institute of Computer Science (IOCS), 2024)
The employment social security program is one of the important programs in providing protection and social security to workers. In an effort to increase the participation of participants in this program, promotion and the quality of services provided by the Employment Social Security Organizing Agency (BPJS) play an important role. In addition, the image of the agency is also a factor that influences participants' decision to join the program. This study aims to investigate the effect of promotion and service quality on participants' decision to join the employment social security program through agency image as an intervening variable. The results showed that promotion and agency image had a significant effect on the decision to join the BPJS Employment program. However, service quality has no significant effect in this study